THE ROLE OF HALAL CERTIFICATES IN THE PERSPECTIVE OF CONSUMER PROTECTION ON OYSTER MUSHROOM NUGET PRODUCTS IN BELAWA VILLAGE - Hafidz Wahyudin; Yosvania Miranda; Muhammad Suhanda (Ann Publisher, 2025)
Abstract Background. MSME actors are one of the economic forces that contribute significantly to the state of Indonesia, especially food-type MSME products. However, many MSMEs still do not have halal certificates when distributing their products. Belawa Village, Cirebon Regency, has the potential to manage oyster mushrooms that have not been used as ready-to-eat products managed by PKK women in Belawa Village. Aims. The goal is that we, as the Thematic KKN Group 15 of Swadaya Gunung Jati University, will develop this potential into oyster mushroom nuggets products and register halal certificates along with NIB as a form of consumer protection, increase market competitiveness and obtain legality and legal certainty. Methods. The method used in this community service is ABCD (Asset-Based-Community Development). Result. The result of the implementation of this service activity is that the activity of making mushroom nuget products is suitable for sale, and a halal certificate has been made along with NIB in collaboration with the participants of Thematic KKN 15 of Swadaya Gunung Jati University with the PKK Women of Belawa Village. Conclusion. In other words, besides being useful in market competition for MSME actors, halal certificates will also increase consumers' confidence in their consumption of these products because they can guarantee product quality, hygiene, cleanliness, comfort, and safety so that consumer health is maintained. Implication. These activities consist of systematically provided training and education until the product is suitable for distribution to the community.